A case of neonatal lupus presenting with myocardial dysfunction with complete heart block: early identification and management results in excellent outcome - Ali, Majid; Beheri, Reem Mohammed; Alheraish, Yasser Abdulrehman; Almuqri, Reyouf; Alarwan, Khaled Mohammed Nasser; Alomair, Maryam Abdulateef Mohammed; Sangi, Rumana; Alawi, Abdulrahman (International Journal of Contemporary Pediatrics, 2025)
Neonatal lupus erythematosus (NLE) is an uncommon acquired autoimmune disorder that develops when maternal autoantibodies to Sjogren’s syndrome A or B (SSA-SSB) autoantigens pass through placenta and cause immune mediated destruction of targeted fetal and neonatal tissues. Among the cardiac abnormalities, congenital complete atrioventricular block (AVB) is the most common cardiovascular abnormality seen in affected fetuses and infants that also accounts for more than 80% of cases of complete AVB in newborns with structurally normal heart. Other cardiovascular manifestations may include arrhythmias, myocarditis, cardiomyopathy and structural heart defects with particular tendency toward valvular lesions. We report a case of a neonate who presented with severe ventricular dysfunction with ejection fraction 20% in the presence of complete heart block (CHB), required extracorporeal membrane oxygenation (ECMO support). After treatment with pulse steroids and IVIG, there was a dramatic improvement in ejection fraction 55%. ECMO support was successfully weaned, and a permanent pacemaker was subsequently inserted. The neonate was discharged home in good health.